Scientific Research and Innovation Driving Forces: An Advanced Study - Baragetti, Sergio (Current Approaches in Science and Technology Research Vol. 10, 2021)
This chapter reports the study of the driving forces acting on scientific research and innovation. Reliability of industrial machines, flying machines and naval equipments rely upon the designer’s capability to assess the role of cracks and defects in the components, and manage them in the life of the mechanical systems. Thus innovation and scientific research are strategic in mehanical design, along with computational mechanics and advance design methods.